Climate Change Worry Among Adolescents Viewed Through Parental Role Perspectives - Kholifah Umi Sholihah; Noor Atika Dewi; Zahrotul Izzah (Universitas Negeri Semarang, 2025)
This study aims to examine differences in adolescents’ climate worry in relation to parental roles. Parental roles in this context refer to parents’ engagement in discussions with their adolescents about climate change and the level of climate-related worry experienced by the parents themselves. The research employed a comparative quantitative method involving 85 adolescent participants. The measurement tool was a translated version of the 10-item Climate Change Worry Scale, which demonstrated a reliability coefficient of 0.858. Data analysis was conducted using the Mann Whitney test. The findings indicated that: (1) There was a significant difference in adolescents’ climate worry based on whether or not parents had engaged in discussions with them. Adolescents whose parents had discussed climate change reported higher levels of climate worry compared to those whose parents had not; and (2) There was a significant difference in adolescents’ climate worry based on parental worry levels. Adolescents with parents who experienced climate worry reported higher climate worry than those whose parents did not. These results suggest that adolescents who engage in climate-related discussions with their parents tend to exhibit higher climate worry, likely because a majority of parents were found to experience climate worry themselves